Menyoal Teks Normatif Seputar Kubur (Kajian Sanad dan Matan Hadis Tentang Ziarah Kubur) - Abusiri Abusiri (Hikmah: Journal of Islamic Studies, 2018)
Until recently, the hadith related to the pilgrimage of the grave is not seldom questioned, both regarding the status of the isnad, quality as well as understanding the contextualism meaning of matan. Because of this, so great that can set about understanding the hadith this grave pilgrimage proportionately, namely when the hadith is understood by textual, contextual, universal, temporal, and local. To find out a comprehensive understanding of the hadith about this grave pilgrimage, it must be known in advance the meaning behind the text or the intent behind the prohibition on grave pilgrimage for women, making it a place of worship, and giving it lights or lighting. This can be done by connecting with other similar verses history or see asbāb al-wurūd of al-hadith is first done after the criticism of matan and isnad. From the study in this article, it appears that at first the grave pilgrimage for women, made the grave a place of worship, and gave it lighting (lights) are indeed prohibited with the intention of keeping the aqidah or monotheism of Allah, preventing dependency to people who have died, and avoid shirk by extolling the grave, and avoid many lamented over their fate and a lack of patience for a woman. But after missing it concerns-severely screwing things, ~ HIKMAH, Vol. XIV, No. 2, 2018 everything should be with the intention of adding to the faith. So, the existence of the ban because of maslaḥah and it’s possible too because of maslaḥah. Keywords: Isnad, Matan, Hadith, Grave Abstrak Sampai saat ini, hadis yang berkaitan dengan ziarah kubur tidak jarang dipersoalkan, baik mengenai status sanad, kualitas matan maupun pemahaman makna kontekstualnya. Karena itu, begitu besar urgensinya bisa mendudukkan pemahaman hadis tentang ziarah kubur ini secara proporsional, yakni kapan hadis tersebut dipahami secara tekstual, kontekstual, universal, temporal, maupun lokal. Untuk mengetahui pemahaman secara komprehensif tentang hadis ziarah kubur ini, harus diketahui terlebih dahulu makna dibalik teks atau maksud dibalik larangan ziarah kubur bagi wanita, menjadikannya sebagai tempat ibadah, dan memberinya penerangan. Hal ini bisa dilakukan dengan cara menghubungkan dengan riwayat lain yang semakna atau melihat asbab al-wurud dari hadis tersebut setelah terlebih dahulu dilakukan kritik sanad dan matannya. Dari kajian dalam artikel ini tampak bawa ziarah kubur bagi wanita, menjadikan kubur sebagai tempat ibadah, dan memberinya penerangan (lampu) pada awalnya memang dilarang dengan maksud memelihara aqidah atau ketauhidan Allah SWT, mencegah ketergantungan kepada orang yang telah meninggal, dan menghindari kesyirikan dengan mengagung-agungkan kubur, dan menghindari banyak keluh kesah dan kurangnya kesabaran bagi wanita. Namun setelah kehawatiran-kekhawatiran itu hilang, semuanya menjadi boleh dengan maksud menambah keimanan. Jadi, adanya larangan karena adanya maslahah dan diperbolehkannyapun karena maslahah. Kata Kunci: Sanad, Matan, Hadis, Kubur